Skin lesion of hidradenitis suppurativa mimicking lymphogranuloma venereum: a case report - Akbar Pratama; Diany Nurdin (Intisari Sains Medis, 2020)
Background: Hidradenitis suppurativa clinical appearance is painful, deep-seated inflamed lesions, most commonly found on axillary, inguinal, anogenital regions. It should be differentiated with primary cutaneous bacterial infection (abscesses, carbuncles, or furunculosis) and rare conditions such as lymphogranuloma venereum.Case: we report a 50-year-old male presenting with an unusual clinical presentation of hidradenitis suppurativa located in suprapubic such as bilateral fluctuant and suppurative nodules resembling lymphadenitis, led to an initial diagnosis of lymphogranuloma. We excluded lymphogranuloma diagnosis based on the serology test of Chlamydia trachomatis, bacterial cultures, and sensitivity tests. The results were non-reactive for the Chlamydia trachomatis serology test, and Staphylococcus aureus was found in bacterial culture.Conclusion: clinicians must be aware of diagnosis precisely, prevent the recurrent, and improve the prognosis.